Economic Aspects of Food Security in Ukrainian Meat and Milk Clusters - Vasylieva, Natalia; Васильєва, Наталя Костянтинівна (AGRIS on-line Papers in Economics and Informatics, 2017)
The goal of the article was to accomplish mathematical estimations of the misbalances and calculate available reserves in providing food security by meat and milk. This issue has considerable economic and social values that imply maintaining agrarians’ welfare and people’s health. The disproportions in meat and milk clusters have been analyzed by means of Lorenz curves and inequality indicators – Hoover and Theil indices, Gini coeficient, and also 20:20 Ratio. It has been grounded that increasing animal productivity and wholesale prices for meat and milk, as well as reducing their retail prices and raising solvency of population would be the essential reserves in supporting food security in the agricultural clusters. The proposed model of defining interregional clusters has made possible to identify the priority options of providing food security and balancing meat and milk supply and demand. All the offered developments and recommendations have been verified at Ukrainian meat and milk clusters. Метою статті була математична оцінка дисбалансу та обчислення досяжних резервів підтримки продовольчої безпеки по м’ясу та молоку. Ця проблема має суттєву економічну та соціальну цінність стосовно забезпечення добробуту аграріїв та здоров’я населення. Диспропорції у м’ясо-молочних кластерах аналізувалися за допомогою кривих Лоренца та індикаторів нерівності індексів Гувера і Тейла, коефіцієнта Джині та відношення 20:20. Обґрунтовано, що збільшення продуктивності тварин та оптових цін на м’ясо і молоко поряд зі зменшенням роздрібних цін та підвищенням купівельної спроможності населення буде суттєвим резервом підтримки продовольчої безпеки по аграрних кластерах. Створена модель визначення міжрегіональних кластерів дозволила ідентифі-кувати пріоритети продовольчої безпеки та збалансувати попит і пропозицію для м’яса і молока. Всі запропоновані розробки та рекомендації протестовані на м’ясо-молочних кластерах України.
Економічні аспекти продовольчої безпеки в українських м’ясо-молочних кластерах
Keywords: food security; продовольча безпека; meat and milk clusters; м’ясо-молочні кластери; indicators of misbalances; індикатори дисбалансу; production and consumption; виробництво та споживання; prices and solvency; ціни та купівельна спроможність; productivity and profitability; продуктивність і рентабельність; cluster model; кластерна модель